2012
DOI: 10.1590/s0103-21002012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Ausências dos colaboradores de enfermagem do pronto-socorro de um hospital universitário

Abstract: Objective: To verify and analyze absences of nursing staff of the adult emergency room (AER) of a university hospital. Methods: A study using a quantitative approach, observational and prospective, conducted between January and December, 2009, involving the nursing staff of a AER. Results: The AER had, on average, 96.8 employees per month. Expected absences corresponded to 30.1% of working days. The absenteeism rate was 11.7%. There was a greater incidence of unplanned absences during the periods of May (15.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
5
0
7
Order By: Relevance
“…(11) The higher prevalence of unplanned absences in the high school level of education category was also observed in another study. (12) There was a relationship between absenteeism and work shift (p = 0,04) in the present study. Research conducted in Spain corroborates these findings.…”
Section: Discussionsupporting
confidence: 50%
“…(11) The higher prevalence of unplanned absences in the high school level of education category was also observed in another study. (12) There was a relationship between absenteeism and work shift (p = 0,04) in the present study. Research conducted in Spain corroborates these findings.…”
Section: Discussionsupporting
confidence: 50%
“…O índice elevado de absenteísmo desorganiza o serviço, gera insatisfação e sobrecarga entre os profissionais, reduz a produção e aumenta o custo operacional, podendo comprometer a qualidade da assistência prestada (SANCINETTI et al, 2011). Nesta perspectiva, outro dado importante relaciona-se à reposição do quadro de pessoal por rotatividade, que é de difícil solução em instituições públicas, posto que o ingresso de pessoal ocorre por meio de concursos públicos esporádicos (FAKIH;TANAKA;CARMAGNANI, 2012). O exposto corrobora a afirmação de Laus e Anselmi (2008), de que não basta às instituições apenas realizarem o cálculo dos percentuais de cobertura se não houver uma identificação conjunta dos determinantes destas ausências, de modo a possibilitar a adoção de estratégias específicas de intervenção.…”
Section: Resultsunclassified
“…Regarding the capacity rates of the emergency hospital service under study, it showed rates that characterized overcrowding in most of the period studied. This characteristic, which is quite common in public emergency services in Brazil, is known to decrease professional satisfaction and quality of care, since the health problems of the Nursing professionals generally have an association with inadequate working conditions (15) . In this way, it is possible to raise the hypothesis that the high occupancy rate in the sector interfered in the leaves of the Nursing workers, even because there were coincidences of a higher volume of leaves with higher rates of service capacity, per month of analysis, in particular the month of August, which was the first among the absences and the second for the capacity rate.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2016 study, whose main objective was to verify the absences of the Nursing staff in the emergency room of a university hospital, showed that Labor Health Leaves (Licenças Trabalhistas de Saúde, LTS) longer than 15 days had the following reasons: mental and behavioral disorders (78.9% of days away), followed by musculoskeletal and respiratory diseases (15) . It should be noted that the present research moves towards demonstrating, based on the multivariate regression model, that only age and musculoskeletal diseases were related to the outcome of leave from 15 days onwards among professionals working emergency hospital service.…”
Section: Discussionmentioning
confidence: 99%